1991
DOI: 10.1203/00006450-199105010-00011
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Ventilation Augments the Left Ventricular Response to Isoproterenol and Volume Loading in Fetal Sheep

Abstract: The basis of this limitation in the ability of the fetal left ventricle to greatly increase output (systolic performance) is controversial. Several studies point to myocardial immaturity: incomplete development of sarcomeres (17-21), decreased functioning of {J-receptors (22, 23), and myofibrillar disarray (24,25) have all been implicated. Although fetal myocardium is certainly immature relative to that of the adult, none of these factors have been shown to change immediately at birth. In addition, many indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There are several possible explanations for this. Although we have previously shown that in utero ventilation with oxygen may increase left ventricular output nearly 3-fold, it does so only when the fetus is supplied with additional blood volume and heart rate is increased by isoproterenol infusion (14). In the present study, plasma catecholamines increased with fetal breathing, but probably not to concentrations comparable to the level of /3-adrenergic receptor activation achieved by isoproterenol infusion.…”
Section: Control Distension Oxygenation Breathingmentioning
confidence: 44%
“…There are several possible explanations for this. Although we have previously shown that in utero ventilation with oxygen may increase left ventricular output nearly 3-fold, it does so only when the fetus is supplied with additional blood volume and heart rate is increased by isoproterenol infusion (14). In the present study, plasma catecholamines increased with fetal breathing, but probably not to concentrations comparable to the level of /3-adrenergic receptor activation achieved by isoproterenol infusion.…”
Section: Control Distension Oxygenation Breathingmentioning
confidence: 44%
“…According to TEYYEL et al [75], myocardial immaturity in fetuses of rabbit, cat and lamb includes incomplete development of sarcomeres, low functioning of beta-receptors, and myoflbrillar disarray.…”
Section: The Irritability Of the Neonate Heartmentioning
confidence: 99%
“…The fetal heart at term is exposed to significant changes in volume and resistance load due to rapid fetal growth and, as a neonate, to the cardiorespiratory adaptation that occurs at delivery. The resultant changes in myocardial performance have been studied in fetal lambs, but the extent to which these acute cardiovascular changes influence perinatal cardiac adaptation has been explored inadequately in humans. Recent advances in cardiac imaging modalities have facilitated an increased interest in rotational mechanics of the heart.…”
Section: Introductionmentioning
confidence: 99%